Kondisi dan Masalah Air di Pulau Jawa - Omo Rusdiana (Institut Pertanian Bogor (IPB University), 2001)
Water is very vital for the life of human beings, animals and plants. At present, the availability of water which have proper quality, has become a serious problem. This phenomenon can be seen from the data issue by DIALOG Journal which described that 1.2 billion people in the world has no acces anymore to clean water. The important impacts of contamination on clean water are among other things : every hour around 400 children suffer from fever, dysentry and cholera. Among those who suffer from such ailments, 37% are helpless and meet their death. In several places in Java island, problems of lack of clean water have been encountered since several years ago. This article discusses the problem of water supply, especially in Java island.